2019
DOI: 10.1002/joc.6395
|View full text |Cite
|
Sign up to set email alerts
|

Vertical variation and temporal trends of extreme precipitation indices in a complex topographical watershed in the Hengduan Mountain Region, China

Abstract: Spatial-temporal trends of extreme precipitation have great impacts on disaster risks, and relevant studies usually receive much attention. In China, spatial-temporal trends have been analysed in numerous studies based on daily rainfall data; however, the densities of rain gauges in many studies were relatively low, and the effects of complex topography on extreme precipitation were usually not considered, which have lowered the reliability and accuracy of the reported results. In this study, several widely us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 59 publications
(82 reference statements)
0
8
0
Order By: Relevance
“…The three extreme precipitation indices (CWD, R10mm, and Rx5day) did not significantly go down, and the three extreme precipitation indices (CDD, R95p, and Rx1day) did not significantly increase. However, extreme precipitation presents apparent regional differentiation on the spatial scale, consistent with Guo's research (Guo et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The three extreme precipitation indices (CWD, R10mm, and Rx5day) did not significantly go down, and the three extreme precipitation indices (CDD, R95p, and Rx1day) did not significantly increase. However, extreme precipitation presents apparent regional differentiation on the spatial scale, consistent with Guo's research (Guo et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Deng et al found that the spatial distribution pattern of climate changes in Qinling Mountains showed significant elevation sensitivity based on the long‐term analysis of climate during 1964–2015, the location of the temperate zone had an apparent vertical upward migration along with the elevation, and the range of migration was more extensive after the abrupt temperature change (mainly in the 1990s) (Deng, ). Guo et al analysed the influence of elevation on extreme climate indices in the Longchuan River basin based on high‐density meteorological stations and they found that with the rise of temperature, the drought trend in high‐elevation areas becomes more apparent and the intensity of single precipitation becomes prominent (Guo et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with longitude and latitude, altitude plays a leading role in the process of extreme climate change in regions with complex topography [60]. Studies have pointed out that extreme weather and extreme hydrological events in plateau and mountainous areas are susceptible to altitude [61]. The trend coefficients of FD0 and ID0 were significantly different above and below the 2112 m elevation boundary, although there was no positive or negative change trend.…”
Section: Influencing Factors (Geographical Factors (Longitude Latitude and Altitude)) Of Extreme Climate Characteristics In Yunnanmentioning
confidence: 99%
“…In addition to the effects of climate variability modes, such as ENSO and PDO, the intense rainfall events over China are also modulated by local forcing factors, for example topography (Shi et al ., 2008; Guo et al ., 2020), and the extreme events over central‐east China are also influenced by tropical cyclones (Zhang et al ., 2018; Cao et al ., 2019a; 2019b). Moreover, the strengthened greenhouse gas emissions derived from human activities during last decades also alter regional rainfall features across China (Ma et al ., 2017; Li et al ., 2017a; 2017b).…”
Section: Conclusion and Discussionmentioning
confidence: 99%